Słowniki i teksty paralelne w przekładzie tekstów prawnych (na wybranych przykładach) - Kościelniak, Robert (Studia Rossica Posnaniensia, 2019)
The purpose of this article is to present the results of the research on the use of dictionaries and parallel texts in the translation process. Examples of collocations in legal texts were used in the research, and the resulting comparison shows the presence (or the absence) of the equivalents of the original units in the respective languages.